Diet of Passerine Birds from different Habitat Types In Sarawak, Borneo - Pang, Sing Tyan; Attiqqah Fadzillah, Sapian; Khatijah, Ismail; Kok, Cze Jhin; Andrew Alek, Tuen (Malaysian Society of Applied Biology, 2018)
Studies on wildlife food resources are important, providing insights into why certain species are abundant while others are not. This is based on the premise that wildlife are attracted to a particular habitat due to abundance of food resources. Small passerine birds inhabit different habitat types in Borneo, but the contribution of diet to this success is seldom investigated. This study aims to determine the diet of the passerine birds in six different habitat types, agro-, secondary, logged, primary, limestone forest and oil palm plantation. 253 individuals from 34 species of passerine birds were captured. Sources for dietary analyses comprised 149 regurgitated, 85 faecal and 33 stomach content samples, which were subsequently examined for prey items. Fifteen orders of prey items were identified, of which 14, 11, 8, 7, 6 and 3 were associated with agro-, secondary, logged, primary, limestone forest and oil palm plantation, respectively. Coleoptera were found eaten by 40% of the birds, followed by Hymenoptera (25%), Arachnidae (9.7%) and Orthoptera (7.5%). Regurgitated samples yielded 15 individuals of intact prey items whereby stomach content and faecal sample had one each. This study showed that Coleoptera are important food for small passerine birds inhabiting different habitats in Sarawak, Borneo.